Pengaruh Capital Intensity Dan Inventory Intensity Terhadap Tax Avoidance : Studi Pada Perusahaan Sektor Transport Dan Logistik Yang Terdaftar Di Bei Tahun 2022-2024 - Muhammad Luthfi Mars Idris Taras; Maria Angie Sianturi; Risma Adelia Remansah; Muhammad Fadli; Linawati Linawati (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of capital intensity and inventory intensity on tax avoidance in transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The independent variables in this study are capital intensity and inventory intensity, while the dependent variable is tax avoidance. This research employs a quantitative approach using panel data regression analysis. The sample was determined through a purposive sampling method, resulting in 20 companies that met the selection criteria over a three-year observation period, yielding a total of 60 observations. The study uses secondary data obtained from companies’ annual financial statements. The results indicate that capital intensity has a negative effect on tax avoidance. Meanwhile, inventory intensity was found to have no significant effect on tax avoidance. These findings suggest that the composition of fixed assets plays a role in tax planning strategies through legally reducing taxable income, whereas inventory levels do not significantly contribute to tax avoidance practices.